2022
DOI: 10.1007/978-3-030-81473-1_5
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced IoT-Based Array of Sensors for Monitoring Patients’ Health

Abstract: The advancement of information technology is demonstrated by the emergence of the Internet of Things, which impacts many areas, such as health care and health services. Internet of Things has grown its branches in nearly all areas due to its enormous characteristics. Due to the current pandemic that has created a gap between doctors and their patients, an intelligent health monitoring system for exact and precise tracking of a patient's health is crucial. Various health monitoring systems are being developed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the year 2022, a novel patient health monitoring device was created utilizing the Internet of Things and four distinct sensors that quantified temperature, heartbeat, pulse, and UV radiation. The study conducted by Odusami et al (2022) revealed that the ESP8266-01 Wi-Fi module data was stored in the cloud via Thing Speak. This approach led to an enhancement of the measured parameters, deployment environment, and response time.…”
Section: Related Workmentioning
confidence: 99%
“…In the year 2022, a novel patient health monitoring device was created utilizing the Internet of Things and four distinct sensors that quantified temperature, heartbeat, pulse, and UV radiation. The study conducted by Odusami et al (2022) revealed that the ESP8266-01 Wi-Fi module data was stored in the cloud via Thing Speak. This approach led to an enhancement of the measured parameters, deployment environment, and response time.…”
Section: Related Workmentioning
confidence: 99%
“…However, recent developments in easy-to-use wearable devices have facilitated continuous long-term monitoring of physiological signals such as ECG or PPG signals [ 25 ]. These technologies augmented with interpretable and accurate artificial-intelligence-based models offer the prospect of not only reducing the cost of monitoring, but also improving patient management through data interpretation and clinical decision support, particularly in low-resource settings [ 26 ].…”
Section: Related Workmentioning
confidence: 99%
“…These drugs can cause side effects such as dry tongue, constipation, loss of appetite, excessive hunger, mild dizziness, stomach irritation, delayed menstruation, excessive/deficient menstrual bleeding [21][22][23]. Also, in the early stages of a serious mental illness, counseling may not be helpful.…”
Section: Introductionmentioning
confidence: 99%